A spent coffee grounds based biorefinery for the production of biofuels, biopolymers, antioxidants and biocomposites. (February 2018) - Karmee, Sanjib Kumar
Highlights: Spent coffee grounds is used as a resource for the preparation of biofuels and value added products. In-situ transesterification of spent coffee grounds show high biodiesel yield. Biopolymer, biosorbent, antioxidant, and biocomposite are obtained from spent coffee grounds. A biorefinery based on spent coffee grounds will positively impact the biobased economy. Circular economy concept can be applied to spent coffee grounds valorisation. Abstract: Spent coffee grounds are composed of lipid, carbohydrates, carbonaceous, and nitrogen containing compounds among others. Using n-hexane and n-hexane/isopropanol mixture highest oil yield was achived during soxhlet extraction of oil from spent coffee grounds. Alternatively, supercritical carbon dioxide can be employed as a green solvent for the extraction of oil. Using advanced chemical and biotechnological methods, spent coffee grounds are converted to various biofuels such as, biodiesel, renewable diesel, bioethanol, bioethers, bio-oil, biochar, and biogas. The in-situ transesterification of spent coffee grounds was carried out in a large scale (4 kg), which led to 80–83% biodiesel yield. In addition, a large number of value added and diversified products viz. polyhydroxyalkanoates, biosorbent, activated carbon, polyol, polyurethane foam, carotenoid, phenolic antioxidants, and green composite are obtained from spent coffee grounds. The principles of circular economy are applied to develop a sustanaible biorefinery based on valorisation of spent coffee grounds.